DEATH BY SEAT BELT COMPRESSION : A CASE REPORT (Journal of Forensic Medicine & Toxicology, 2024)
Background: With the advent of car seat belts, there has been a significant decrease in the number of deaths due to car accidents. However, two unique patterns of injuries, the ‘seat belt sign’ and ‘seat belt syndrome’ have emerged. Fractures of the sternum, rib cage, clavicles, and injuries to abdominal organs are potential injuries that may occur. Case: We are presenting the case of a 25-year-old male who was a restrained rear-seat passenger in a car versus truck collision, brought for a medical-legal autopsy. The physical examination showed a diagonal contusion across the chest and a horizontal contusion on the abdomen. Upon careful examination, we observed the presence of the ‘seat belt sign’ and ‘seat belt syndrome’. Conclusion: The diversity of organ injuries due to seat belts includes all possible combinations, and the deceased with a seat belt sign have a higher likelihood of having internal injuries.
Keywords: Accidents; Seat belt; Autopsy